FEATURES OF LOGISTICS SERVICE - REZNIK, NADIA; PIVEN, ALONA; VOLOSHINA, ALEXANDRA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article reveals the concept, meaning and essence of logistics service, work on providing a range of services (the process of ordering, purchasing, supply and subsequent maintenance of products), quality indicators. The category "logistics system" is revealed using the morphological - semantic method and the classification features of the logistics service are generalized. The service as an important component of logistical support of the enterprise is analyzed. As a result of low level of development of logistics services in Ukraine and reduction of efficiency of logistics activity of trade enterprises the preconditions of development of logistics in trade are defined, expediency of research of changes of external environment is proved and the system of indicators reflecting a condition and dynamics of demand in the wholesale and retail market is proved. , the level of competition in the segment of trade enterprises. The expediency of considering logistics services with compliance with process-functional approaches, which allowed to define logistics activities as a set of processes for the implementation of functional tasks and management decisions, formed taking into account the goals of enterprises in the field of logistics. It is determined that the decisive tool of marketing and strategic means of improving competitive positions in the commodity market is customer service in the process of order fulfillment. It is noted that the improvement of service should take place throughout the logistics chain, harmonizing the relationship between technological components and elements of logistics systems. The purpose of this article is to analyze the essence of logistics service and the features of logistics during the product cycle.